The Midwife Toad Challenge After (Half) a Century - Arntzen, Jan W. (Frontiers in Ecology and Evolution, 2022)
The evolutionary biologist Paul Kammerer (1880–1926) purportedly demonstrated that environmentally induced character states are carried over to the next generation(s), therewith providing evidence for Lamarckian evolution. Kammerer’s work is generally seen as contentious but has also been valued as daring and insightful, and Kammerer has been heralded as an academic forebear of epigenetics. Most of the more pertinent of Kammerer’s experiments on amphibians and the sea squirt have either been invalidated by replications that failed, or have been dismissed as virtually impossible. An experiment on color pattern change in the fire salamander stands out because it has been confirmed, but only with data for within a generation, so that Kammerer’s claim concerning the inheritance of acquired character states still awaits confirmation. To facilitate and encourage replicate studies, I draw attention to species and populations that would be most practical and promising to work with, for those that are into the challenge.